Réponses

2014-01-12T11:17:45+01:00
Bonjour,

f(x)=2x+\dfrac{1}{3}

1)  f(\dfrac{5}{3})=2\times\dfrac{5}{3}+\dfrac{1}{3}\\\\f(\dfrac{5}{3})=\dfrac{10}{3}+\dfrac{1}{3}\\\\f(\dfrac{5}{3})=\dfrac{11}{3}\\\\\\\\f(\dfrac{-11}{3})=2\times(\dfrac{-11}{3})+\dfrac{1}{3}\\\\f(\dfrac{-11}{3})=\dfrac{-22}{3}+\dfrac{1}{3}\\\\f(\dfrac{-11}{3})=-\dfrac{21}{3}\\\\f(\dfrac{-11}{3})=-7

L'image de 5/3 par f est égale à 11/3.
L'image de -11/3 par f est égale à -7.

2) Résoudre l'équation  2x + 1/3 = 1/3
2x = 1/3 - 1/3
2x = 0
x = 0/2
x = 0

L'antécédent de 1/3 par f est égal à 0.